Low-dose abdominal computed tomography for detection of urinary stone disease − Impact of additional spectral shaping of the X-ray beam on image quality and dose parameters. Issue 6 (June 2016) - Dewes, Patricia; Frellesen, Claudia; Scholtz, Jan-Erik; Fischer, Sebastian; Vogl, Thomas J.; Bauer, Ralf W.; Schulz, Boris
Abstract: Objectives: To evaluate a novel tin filter-based abdominal CT protocol for urolithiasis in terms of image quality and CT dose parameters. Methods: 130 consecutive patients with suspected urolithiasis underwent non-enhanced CT with three different protocols: 48 patients (group 1) were examined at tin-filtered 150 kV (150 kV Sn) on a third-generation dual-source-CT, 33 patients were examined with automated kV-selection (110–140 kV) based on the scout view on the same CT-device (group 2), and 49 patients were examined on a second-generation dual-source-CT (group 3) with automated kV-selection (100–140 kV). Automated exposure control was active in all groups. Image quality was subjectively evaluated on a 5-point-likert-scale by two radiologists and interobserver agreement as well as signal-to-noise-ratio (SNR) was calculated. Dose-length-product (DLP) and volume CT dose index (CTDIvol) were compared. Results: Image quality was rated in favour for the tin filter protocol with excellent interobserver agreement (ICC = 0.86–0.91) and the difference reached statistical significance (p < 0.001). SNR was significantly higher in group 1 and 2 compared to second-generation DSCT ( p   <   0.001 ). On third-generation dual-source CT, there was no significant difference in SNR between the 150 kV Sn and the automated kV selection protocol (p = 0.5). The DLP of group 1 was 23% and 21% (p < 0.002) lower in comparison to group 2 and 3, respectively. So was the CTDIvol of group 1 compared to group 2 (−36%) and 3 (−32%) (p < 0.001). Conclusion: Additional shaping of a 150 kV source spectrum by a tin filter substantially lowers patient exposure while improving image quality on un-enhanced abdominal computed tomography for urinary stone disease.